Epigenetic variation in light of population genetic practice - Sarah A. Mueller; Justin Merondun; Sonja Lečić; Jochen B. W. Wolf (Nature Communications)
Abstract The evolutionary impact of epigenetic variation depends on its transgenerational stability and source - whether genetically determined, environmentally induced, or due to spontaneous, genotype-independent mutations. Here, we evaluate current approaches for investigating an independent role of epigenetics in evolution, pinpointing methodological challenges. We further identify opportunities arising from integrating epigenetic data with population genetic analyses in natural populations. Efforts to advance data quality, study design, and statistical treatment are encouraged to consolidate our understanding of the source of heritable epigenetic variation, quantify its autonomous potential for evolution, and enrich population genetic analyses with an additional layer of information.